Effects of Lubricant Composition on Adsorption Behavior of Proteins on Rubbing Surface and Stability of Protein Boundary Film - Seido Yarimitsu (Japanese Society of Tribologists, 2008)
Polyvinyl alcohol (PVA) hydrogel is one of the candidate materials for artificial cartilage. In previous research, it was found that the structure of protein boundary film is important essence for wear reduction of PVA hydrogel, and the stability of protein boundary film changes with relative ratio and total concentration of proteins. In this study, the behavior of protein adsorption on the glass surface rubbed with PVA hydrogel was observed by using total internal reflection fluorescence microscopy (TIRFM). Amount of adsorbed proteins under rubbed condition increased compared to those under statically immersed condition. In lubricant in which a stable protein boundary film was formed, the amount of adsorbed proteins in bottom layer of protein boundary film increased significantly with an increase of sliding distance. In addition, the ratio of adsorbed immuno globulin G (IgG) to albumin was higher than that in lubricant in which an exfoliative protein boundary film was formed. These results indicate that the formation of bottom layer mainly composed of γ-globulin is a critical element to form a stable boundary film, and the friction-induced enhancement of forming protein boundary film may occur in lubricant with appropriate protein constituents.